Sustainable Alternatives to Polyethylene (PE) for Medical Applications: A Fuzzy Multi-Criteria Decision-Making Approach - EL HALLAB, SOULAYMA (İstanbul Kültür Üniversitesi, 2025)
This research tackles the major environmental issues presented by polyethylene (PE) plastics in healthcare settings by creating a thorough assessment framework for sustainable substitutes. Although PE is commonly used in medical packaging and devices (25-30% of medical plastics), its origin from petroleum and low recyclability lead to significant environmental harm. Employing a fuzzy multi-criteria decision-making approach, the study assessed four possible options: Bio-PE, PLA, PBS, and PHA, based on six essential criteria: environmental influence, expense, quality, accessibility, regulatory conditions, and performance alignment. The framework incorporated Fuzzy Analytic Hierarchy Process (F-AHP) for assessing criteria weights from expert evaluations and employed Fuzzy Technique for Order Preference by Similarity to Ideal Solution (F-TOPSIS) for ranking the alternatives. Findings showed Bio-PE to be the best option with a closeness coefficient of 0.517, succeeded by PLA (0.495), PBS (0.433), and PHA (0.372). Bio-PE exhibited outstanding overall performance thanks to its excellent regulatory adherence, high-quality attributes, and technical capabilities like traditional PE, while providing a reduction in carbon footprint of up to 75%. Sensitivity analysis validated the strength of these results in different prioritization scenarios. Future studies may concentrate on broadening the assessment framework to encompass more emerging biomaterials, performing physical tests and clinical trials of the selected alternatives in particular medical applications, and creating advanced cycle assessment models that reflect the total environmental impact throughout regional healthcare systems.
Keywords: Sustainable Plastics; Healthcare Sustainability; Material Selection; Bio-Based Polymers